THE ADVANCING SAFETY AND COMFORT WRIST GUARD USING GEL PAD AND NYLON - ZUNUWANAS, MUHAMMAD RIDZUAN AMIR BIN ZUNUWANAS; AHMAD YASSIN, WARDAH BINTI AHMAD YASSIN; BASRI, MUHAMMAD AMIRUL HAKEEM BIN BASRI; MOHAMAD, ZUNUWANAS BIN MOHAMAD (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
Wrist fractures, often resulting from falls or high-impact activities, pose a significant health concern. Wrist guards, designed to reduce the risk of fractures, have become an important protective tool. This study examines the influence of materials on the effectiveness and performance of wrist guards in fractures including Gel pads, Neoprene and Nylon materials. Additionally, the ergonomic aspects of material selection to ensure wearer comfort and compliance, important factors for the practical use of wrist protectors. This design aims to provide a brief overview of the current state of knowledge regarding wrist protective materials and their role in fractures also improving the effectiveness of wrist protectors, thereby increasing their utility across a variety of contexts, including occupational safety, and daily activities. KEYWORDS: Wrist Guard, Gel Pad, Nylon, Neoprene.